The Relative Contribution of Compassionate Communication to Psychological Empowerment in Emerging Families - Almfarriji, Salem Mohammed; Alotaibi, Dhafallah M (Journal of Posthumanism, 2025)
The research aims to reveal the relative contribution of compassionate communication to psychological empowerment among emerging families. To achieve the research objective, a correlational descriptive method was used to verify it. The compassionate communication scale and the psychological empowerment scale were applied to a sample of 192 newly emerging families, particularly wives who recently married in the city of Mecca. The results showed that the level of compassionate communication and psychological empowerment among the wives in the sample was average. The results also revealed a positive impact of compassionate communication (overall score and dimensions) on psychological empowerment, The results also indicated statistically significant differences among the wives in the research sample regarding psychological empowerment based on age, favoring those whose age was less than 25 years. Additionally, there were statistically significant differences among the wives based on the duration of their marriage, favoring those whose marriage duration was less than two years. Furthermore, there were statistically significant differences among the wives in the four levels of compassionate communication regarding the wife's psychological empowerment, favoring those with high compassionate communication.